Septal Aperture of the Humerus: Etiology and Frequency Rates in Two European Populations. Issue 7 (23rd October 2019) - Bradshaw, Rebecca; Eliopoulos, Constantine; Borrini, Matteo
ABSTRACT: Analysis of the septal aperture was conducted on two documented European populations. Collections from the National Museum of Natural History Lisbon, Portugal, and University of Athens, Greece, were used for the study. Both collections are modern and documented for sex and age. The Portuguese sample comprises 297 individuals (149 males and 148 females) between the ages of 18 and 88. A septal aperture was observed in 50 individuals resulting in a frequency of 16.83%. The Greek sample comprises 117 individuals (68 males and 49 females) between the ages of 20 and 65. Twenty‐five septal apertures were observed, giving a frequency of 21.37%. Both populations had high frequencies which exceeded those observed in European countries in previous studies. Sex analysis shows that both samples confirm that septal apertures are more common in females. The Portuguese sample also supports that septal apertures are more common in the left humerus; however, the Greek sample had a higher frequency of bilateral cases. Measurements of the Portuguese sample were taken to determine whether robusticity correlates with presence of septal apertures. These measurements concluded that there was no difference in robusticity with presence or absence of a septal aperture, challenging previous studies. Anat Rec, 2019. © 2019 American Association for Anatomy Anat Rec, 303:1821–1830, 2020. © 2019 American Association for Anatomy